Full-scale multipurpose ozonation in urban wastewater with strong textile input: removal of colour, micropollutants, pathogens and antimicrobial resistance indicators - Margarida Campinas; Ivone Vaz-Moreira; Rui M.C. Viegas; Elsa Mesquita; Diana Ribeiro; Afonso Ruivo; Joana Soares; Paula Paíga; Cristina Delerue-Matos; Gabriela Faria; Catarina Silva; Cláudio Costa; et al. (Desalination, 2026)

Wastewater Sludge-Derived Adsorbents for Landfill Leachate Treatment - I. Oliveira; M. Bernardo; M. Rocha; I. Matos; I. M. Fonseca; N. Lapa (Environmental Processes, 2026)

Time in the city: long-term urban exposure predicts greater exploration and problem solving in wild red foxes - F. Blake Morton; Dylan Thompson-Jones; Kristy A. Adaway; Koko M. Sutter; Catia Matos; Georgia B. Freer; Georgia A.A. Fletcher; Carl D. Soulsbury (Animal Behaviour, 2026)

Nanoplastics influence on toxic metal bioaccumulation and antioxidant responses in Lactuca sativa L. irrigated with treated wastewater - A.M. Barreiros; H.F. Silva; L. Araújo; J. Coelho; C.M. Oliveira; N. Silva; M. Matos; S. Piçarra (Science of The Total Environment, 2026)

Mitral annular plane systolic excursion to left atrial volume ratio as a novel index to assess ventricular filling pressure in dogs with myxomatous mitral valve disease - Jeff M. Perez; Jorge Isidoro Matos; Oscar Monge-Utrilla; Pablo Fernandez-Rodriguez; Soraya Falcon-Cordon; Javier Engel-Manchado (Veterinary Research Communications, 2026)

The genus Pouteria: a review of advances in phytochemical elucidation and its pharmacological properties - Rafael C. Matos; Ana Flavia A. Bitencourt; Vanessa R. Prado; Alexsandro D. M. Oliveira; Renes R. Machado; Marina Scopel (Phytochemistry Reviews, 2026)
The genus Pouteria (family Sapotaceae) is traditionally used for gastrointestinal, inflammatory, and microbial issues, and has great nutritional applications because of the variety of fruits it contains. Despite its versatile applications, comprehensive research on Pouteria remains outdated, necessitating an integrative review of recent studies exploring its phytochemical evidence and biological activities. An unrestricted search in various databases (Jan/2009 to Aug/2022) focused on the genus “ Pouteria ”. Despite this genus having 325 recognized species, few studies have evaluated their bioactive potential, including antioxidant, anticancer, hypoglycemic, antimicrobial, anti-inflammatory, and antinociceptive, as well as their potential for treatment of Alzheimer disease. Regarding phytochemical evaluation, among the few substances isolated were a high number of terpenoids, flavonoids, phenolics, saponins, and others. In addition, owing to the high potential for fruit utilization, several primary metabolites were identified, which presented qualitative and quantitative diversity among species with the interests of the pharmaceutical industry. Therefore, this review provides information about phytochemical and pharmacological properties of the species of Pouteria . Given the shallow and incomplete results for several species, there is a demonstrated need for new studies encompassing all plant parts of Pouteria species, contributing to a more comprehensive understanding of their medicinal potential.

Can large language models implement agent-based models? An ODD-based replication study - Nuno Fachada; Daniel Fernandes; Carlos M. Fernandes; João P. Matos-Carvalho (Ecological Modelling, 2026)

Migration of ionic and nanoparticulate zinc from nanocellulose/ZnO nanoparticle films: morphology-dependent behaviour and modelling - Ana Rita Mendes; Otmar Geiss; Ivana Bianchi; Jessica Ponti; Ana Matos; Cristina L. M. Silva; Fátima Poças (Food Additives & Contaminants: Part A, 2026)

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

Corrigendum to “Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil)” [J. Geochem. Explor. 281,107934 (2026)] - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Designing ZnS-based photocatalytic systems: From defect engineering to structure–Activity relationships and functional applications - Felipe M. Pinto; Lucas Bonfim-Rocha; Glaura S.A. Fernandes; Roberto Matos; Fernando Wypych; Felipe A. La Porta (Journal of Environmental Chemical Engineering, 2026)

Concrete Jungle: habitat heterogeneity acts as environmental filter on multidimensional diversity of fruit-feeding butterflies in urban Savannahs of Cerrado biome - Geraldo de Brito Freire; Israel Pereira dos Santos Ribeiro; Ana Carolina Lacerda de Matos; Sofia Coradini Schirmer; Eduardo Guimarães Santos; Fernanda Vieira da Costa; Felipe M. Gawryszewski; Lee A. Dyer; Onildo J. Marini-Filho; Pedro Togni (Urban Ecosystems, 2026)

Unveiling the Hidden Biotechnological Potential of the Vermetid Gastropod Vermetus triquetrus: Insights into an Unexplored Marine Resource - A. Breves; C. Cardoso; C. Afonso; J. Matos; J. Lobo-Arteaga; C. Bartilotti; S. Sales; S. Pedro; N. M. Bandarra (Marine Biotechnology, 2026)
The vermetid Vermetus triquetrus , commonly found on intertidal hard substrates in the Mediterranean Sea and the Portuguese coast, remains an underexplored marine resource. This study aimed to determine the total polyphenol content, fatty acid (FA) composition, and biological activity (antioxidant and anti-inflammatory properties) in the visceral mass and the head-foot part of this sessile gastropod from a population collected in Mira Estuary, mainland Portugal. The FA profile of the visceral mass albeit rich in saturated FA had significant levels of long-chain polyunsaturated FA, arachidonic acid (20:4 ω6), 6.3%, and eicosapentaenoic acid (20:5 ω3, EPA), 4.2% of total FA, and a non-negligible content of docosapentaenoic (22:5 ω3), 2.1%. Moreover, though the FA profile of the head-foot part was not attained, regarding other parameters, there were differences between the visceral mass and head-foot part of V. triquetrus. In fact, concerning polyphenol content, whereas the head-foot contained a total of 142 ± 14 mg GAE/100 g dw, the visceral mass reached a high level of 314 ± 90 mg GAE/100 g dw. The antioxidant activity as measured by FRAP showed a similar pattern of higher values in the visceral mass than in the head-foot, 55.6 ± 18.3 µmol Fe2+/g dw vs. 9.8 ± 0.8 µmol Fe2+/g dw. Finally, the ABTS methodology largely agreed with polyphenol levels and FRAP, being the head-foot with 1189 ± 223 µmol Trolox Eq/100 g dw less antioxidant than the visceral mass, 5511 ± 2304 µmol Trolox Eq/100 g dw. Given the presence of anti-inflammatory compounds, such as polyphenols (more abundant in the visceral mass), anti-inflammatory activity, as measured by COX-2 inhibition %, was detected, reaching more than 30% in the visceral mass. Therefore, the gastropod V . triquetrus can be a source of polyphenolic compounds, being specially its visceral mass, not only a rich source of polyphenols, but also a starting material for highly antioxidant extracts. Given the known biological activity of polyphenols and the convergence of results with the FRAP and ABTS antioxidant activity methods, further study on the specific phenolic composition and extract fractionation and refining is warranted.

Native Trichoderma spp. as biocontrol agents against common beans anthracnose - S. C. Izidoro-Morimitsu; A. Knob; C. K. Matos; C. M. D. R. Faria; J. Kawakami (Journal of Plant Diseases and Protection, 2026)

Plant antimicrobials: extraction, characterization and activity against foodborne microorganisms - Fabiana França; Júlia Campos de Souza; Paula M. O’Connor; Andreia Pereira Matos; Natan de Jesus Pimentel-Filho (Folia Microbiologica, 2026)

Degradability, Phytotoxicity, and Life Cycle Assessment of Chestnut Waste Biocomposites - Simão B. Silva; Samara Rodrigues; Elena Surra; Elsa Vieira; Cristina Delerue-Matos; Olga M. Freitas; Valentina F. Domingues (Environmental Processes, 2026)

Mitochondrial Fumarase mRNA expression changes under Al stress in the genus secale and Brachypodium distachyon - Diaa Abd El-Moneim; Elisabete Santos; Roberto Contreras; Ana M. Figueiras; Manuela Matos; César Benito (Cereal Research Communications, 2026)

Correction to: Comparative genomics of Sphingomonas from the cupuassu (Theobroma grandiflorum) phyllosphere reveals signatures of host adaptation and beneficial interactions - Ana Karla da Silva; Camila Henriques de Paula; Jéssica Pereira de Matos; Dilson Fagundes Ribeiro; Isabella Ferreira Cordeiro; Camila Gracyelle de Carvalho Lemes; Angélica Bianchini Sanchez; Camila Carrião Machado Garcia; Vinicius A. C. de Abreu; Rafael Moysés Alves; Mauro de Medeiros Oliveira; João Victor dos Anjos Almeida; et al. (Symbiosis, 2026)

Valorization of by-products from the wastewater sector through anaerobic Co-digestion following the circular economy principles - Andreia D.M. Silva; Ricardo Couto; Margarida Silva; Raquel T. da Silva; João Vilaça; Sónia A. Figueiredo; Olga M. Freitas; Nídia S. Caetano; Cristina Delerue-Matos (Biomass and Bioenergy, 2026)

Ready to eat, ready to risk? A retrospective evaluation of microbiological contamination and surveillance gaps in self-service meals in Bahia, Brazil - Joselene C.N. Nascimento; Danilo M. Vilas-Boas; Clícia C. Leite; Victor O. Martinez; Juliana R. Matos; Mariana N. Roselino; Cleber A. Schmidt; Wilson J.F. Lemos Junior; Anderson S. Sant’Ana; Alaíse G. Guimarães (Food Control, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Comparative genomics of Sphingomonas from the cupuassu (Theobroma grandiflorum) phyllosphere reveals signatures of host adaptation and beneficial interactions - Ana Karla da Silva; Camila Henriques de Paula; Jéssica Pereira de Matos; Dilson Fagundes Ribeiro; Isabella Ferreira Cordeiro; Camila Gracyelle de Carvalho Lemes; Angélica Bianchini Sanchez; Camila Carrião Machado Garcia; Vinicius A. C. de Abreu; Rafael Moysés Alves; Mauro de Medeiros Oliveira; João Victor dos Anjos Almeida; et al. (Symbiosis, 2026)

Corrigendum to “Microplastic pollution across the Brazilian coastline: Evidence from the MICROMar project, the largest coastal survey in the Global South” [Environ. Res. 286, Part 2, (2025) 122923] - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Environmental Research, 2026)

Prospection of Autochthonous Lactic Acid Bacteria Displaying Probiotic Potential to Enhance Colossoma macropomum Larvae Growth and Immunoprotection Against Aeromonas hydrophila - Thayná M. dos Santos; Layana A. B. Pereira; Laine P. C. dos Santos; Andrya L. Lopes; Larissa A. F. Sampaio; Graziella V. G. de Matos Silva; Juliana N. Ferreira; Gleika T. J. Dos Reis; Jonny B. Teixeira; Raimundo J. T. Diniz‐Neto; Laura G. M. de Carvalho; Michelle Midori Sena Fugimura; et al. (Journal of Fish Diseases, 2026)
This study assessed the functional potential of autochthonous lactic acid bacteria isolated from the gastrointestinal tract of tambaqui ( Colossoma macropomum ) as larviculture probiotics. Five strains were selected and identified as belonging to the genus Weissella . In vitro assays revealed high tolerance to acidic pH (2.0–3.0), resistance to bile salts (10%), biofilm formation capacity, hydrophobicity and direct Aeromonas hydrophila inhibition. In in vivo tests, strains M13 and M14 promoted significant increases in tambaqui survival (72.2% and 68.7%; p

Correction to: Plant antimicrobials: extraction, characterization and activity against foodborne microorganisms - Fabiana França; Júlia Campos de Souza; Paula M. O’Connor; Andreia Pereira Matos; Natan de Jesus Pimentel-Filho (Folia Microbiologica, 2026)

Microplastic pollution in Brazil's coastal marine surface waters: The first macroregional baseline from the global south - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Marine Pollution Bulletin, 2026)

Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil) - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Evaluating quality of novel alternative protein sources (microbial and insect proteins) using the INFOGEST in vitro digestion model - Rebecca Graham; Ally Motta de Matos; Tim Parr; John M. Brameld (Food Chemistry, 2026)

BK polyomavirus in a Portuguese healthy group: seroprevalence, viral Excretion, and implications for transmission pathways - Joana M. Oliveira; Daniela Veiga; Sara Pereira; Cristina Luxo; Ana Miguel Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Seamounts of Cabo Verde: A review of their ecological and economic significance, anthropogenic impacts, and conservation needs - Covadonga Orejas; Beatriz Vinha; Gillian B. Ainsworth; Sarah Saldanha; Teresa Militão; Christian Mohn; Thor H. Hansteen; Sara S. Ratão; Henk-Jan Hoving; Teresa Amaro; Dominique M.J. Anderson; Deusa Araújo; et al. (Progress in Oceanography, 2026)

Multifunctional N,S-doped biochar decorated with transition metals as electrocatalysts for energy conversion applications - Renata Matos; Inês S. Marques; António J.S. Fernandes; Andreia F. Peixoto; Diana M. Fernandes (Biomass and Bioenergy, 2026)

Microplastic pollution across the Brazilian coastline: Evidence from the MICROMar project, the largest coastal survey in the Global South - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Environmental Research, 2025)

Flood-Fire Interplays in Wetlands: The Rising of an Actionable Field of Study - Geraldo Alves Damasceno-Junior; Alexandre de Matos Martins Pereira; Bambang Hero Saharjo; Sally Archibald; Beibei Zhang; Bibiana Bilbao; Bruno Henrique dos Santos Ferreira; Carol Kagaba Kairumba; Danilo Bandini Ribeiro; David G. Campbell; Denis Mburu Njoroge; Dennis Twinomujuni; et al. (Wetlands, 2025)
Floods and fires are part of the ecological regime in many wetlands, yet their interconnectedness is poorly explored. Climate extremes, such as droughts and heatwaves, are increasing fire frequency and intensity, while changing rainfall patterns make floods more unpredictable. These events shape wetland physiognomy, species composition, and functioning. Different wetlands experience varying fire exposure; seasonally inundated grasslands burn almost annually, whereas tropical forests rarely catch fire. Some wetlands are more resilient to fire, drought, and floods than others. Communities dependent on wetlands possess ecological knowledge that supports adaptation, enhancing ecosystem resilience. Though often studied separately, floods and fires in wetlands are interrelated. In addition to environmental aspects, social, cultural and associated traditional knowledge dimensions must be included in conservation processes for these environments. A holistic understanding is crucial for conservation. Researchers from sixteen countries propose a new field of study on flood-fire interactions to improve wetland management and sustainability.

Geochemistry of the volcano-sedimentary complex of the Algarve Basin (Silves-Ayamonte, SW Iberia) - A. Díez-Montes; R. Solá; J. J. Huerta; S. Machado; R. Dias; J. X. Matos; M. López (Journal of Iberian Geology, 2025)
The Volcano-Sedimentary Complex of the Algarve basin (south of the Iberian Peninsula) belongs to the Large Igneous Province of the Central Atlantic Magmatic Province (CAMP), which developed c.200 Ma following the start of the breakup of Pangaea, and preceding the opening of the Atlantic Ocean. This volcanic complex was emplaced in a short period of time in the Lower Jurassic (Hettangian-Sinemurian). It includes subaerial lava flows, pyroclastic deposits and peperites, and contemporaneous sedimentation. We present new field evidence and geochemical data of mafic rock suites within a > 150 km long transect across the volcanic belt. The rocks have a subalkaline geochemical affinity and low TiO 2 contents. They are moderately evolved (Mg# 53–76) and have quartz-hypersthene-normative associations, classifying as low-Ti tholeiites (TiO 2 = 1.2–1.5 wt%). They have slight yet variable enrichment in light ion lithophile and light rare erath elements [(La/Yb) N = 2.55–3.40] and a negative Ta-Nb anomalies. The mafic rocks have enriched MORB compositions, compatible with low-Ti tholeiitic CAMP suites. A trait of CAMP basaltic flows is their compositional homogeneity. Distinct volcanic rocks are only described in the Algarve basin, and have relatively lower SiO 2 and high CaO contents than typical CAMP rocks. Our data suggest that the subset of volcanic rocks with lower SiO 2 and high CaO are linked to contamination-assimilation of ascending magmas with carbonate-evaporite material from Silves marl-carbonated-evaporitic complex, immediately underlying the CAMP sequences.

Bovine and ovine deltapapillomavirus coinfection associated with equine sarcoid - E. L. Pereira; G. R. Pereira; M. L. de Osório; J. L. A. Terra; J. B. Gayger; J. S. Gularte; M. Demoliner; V. M. A. G. Pereira; M. Filippi; Q. S. de Matos; A. Tessman; C. W. Canal; et al. (Brazilian Journal of Microbiology, 2025)

The goat Longissimus thoracis et lumborum muscle proteome: effects of dry ageing and cooking in chevon - Menalda Valeriano André; Catarina Prista; Vítor D. Alves; David M. Ribeiro; Miguel Filipe Pedro; Laura Sacarrão-Birrento; Hugo Osório; André M. de Almeida; Teresa J.S. Matos (Food Research International, 2025)

Evaluation of different small-scale constructed wetlands cultivated with ultrashort hydraulic retention time and reduced operational control - R. A. Crippa; M. S. Ázara; M. P. Matos; A. T. Matos; R. Fia; L. C. Lima; A. L. P. Valácio; T. R. Silva (International Journal of Environmental Science and Technology, 2025)

Here, There and Everywhere: Widespread Non‐Native Plants in the World's Urban Ecosystems - David M. Richardson; Lauren B. Trotta; Myla F. J. Aronson; Benjamin Baiser; Marc W. Cadotte; Marta Carboni; Laura Celesti‐Grapow; Sonja Knapp; Ingolf Kühn; Ana Carolina Lacerda de Matos; Zdeňka Lososová; Daijiang Li; et al. (Global Ecology and Biogeography, 2025)
Aim To (a) produce a list of the most widespread naturalised non‐native plant species across cities of the world; (b) explore whether cities on different continents are invaded by the same group of widespread naturalised species; and (c) elucidate the origins of the most widespread naturalised urban species. Location Global. Time Period No specific period. Major Taxa Studied Vascular plants. Method Using the most comprehensive and up‐to‐date dataset of non‐native urban floras yet assembled (GUBIC; Global Urban Biological Invasions Compendium), we identified the most widespread naturalised plant species (the global urban florome) by filtering for taxa present across all continents (except Antarctica) and their frequency in urban areas. To assess global patterns of urban plant naturalisation, we conducted ordination analyses and visualised species co‐occurrence. We also examined species origins and their environmental impact. Results Among the 7792 naturalised plant species recorded in 553 urban centres, 302 species (4%) were found on all six continents. Of these, 96 species, considered the most widespread species, were present in more than half of urban centres in Oceania, North America and South America; this proportion was higher than in Africa, Asia and Europe. Cities outside Europe and Asia are more homogeneous in terms of the species composition of the most widespread invaders. An analysis of species origins showed that temperate Asia contributed the most species globally, while intercontinental exchange patterns varied, with a notable one‐directional flow from North to South America. Main Conclusions Our results suggest that urban ecosystems outside Europe and Asia are more susceptible to recent invasions than those within these two continents. Understanding the composition and origins of these widespread species is crucial for developing coordinated management strategies and improving the resilience of urban biodiversity.

PKC-α activation with new semi-synthetic 7α-acetoxy-6β-hydroxyroyleanone derivatives for breast cancer therapeutics - Vera M. S. Isca; Ana C. Matos; Joana Almeida; Lucília Saraiva; Carlos A.M Afonso; Patrícia Rijo (Phytochemistry Letters, 2025)

Combining residual iron dust and biomass fly ash as in-situ waste-based catalysts to promote tar reduction and enhance producer gas quality from biomass steam gasification - Helena G.M.F. Gomes; Daniela V. Lopes; João P. Ribeiro; Jéssica M. Moura; Nuno M.C. Cruz; Aleksey Yaremchenko; Maria I. Nunes; Manuel A.A. Matos; Luís A.C. Tarelho (Journal of Cleaner Production, 2025)

Rapid and high-throughput UHPLC-DAD method for simultaneous quantification of 38 polyphenols in applewood - Hannes Withouck; Axel Paelinck; Manuela M. Moreira; Cristina Delerue-Matos; Imogen Foubert; Ilse Fraeye (Food Bioscience, 2025)

The role of nest-site interference competition with Cape Verde Shearwater in explaining breeding success of Red-billed Tropicbird on Raso Islet, Cape Verde archipelago - Jaime A. Ramos; Catelene Monteiro; Isabel Rodrigues; Diana M. Matos; Vitor H. Paiva; Filipe R. Ceia; Jorge M. Pereira; Kenny Delgado; Stefan Antunes (Journal of Ornithology, 2025)

Unveiling the Secret: Effect of Grape Stems as Soil Amendments in Earthworm Tail Regeneration and Reproductive Success - Tiago Azevedo; Marta Roboredo; Ana I. R. N. A. Barros; Irene Gouvinhas; Lara Anjos; Rafael Araújo; João R. Sousa; Isabel Gaivão; Maria de Lurdes Pinto; Manuela Matos; Francisco Peixoto; Maria Manuel Oliveira; et al. (Journal of Soil Science and Plant Nutrition, 2025)
The increasing reliance on agricultural machinery to improve agronomic output and meet food demands disrupts soil structure and poses risks to soil biota, including mechanical injuries to earthworms. This study assesses the potential of grape stems as a soil amendment to promote earthworm regeneration and investigate their impact on reproduction and oxidative stress. Four experimental conditions were established: a control group (E0) with OECD reference soil and three groups where ground grape stems replaced 5% (E5), 10% (E10) and 25% (E25) of peat. Earthworms ( n = 10/replicate) were amputated 30 segments past the clitellum. Destructive sampling occurred at 15, 30, and 45 days post-amputation. Regenerated segments were measured/counted, while adjacent tissue and blastema were analysed for oxidative stress markers (catalase (CAT), glutathione S-transferase (GST), peroxidase (POD), superoxide dismutase (SOD) activities). Reproductive output was assessed 60 days post-amputation. Regeneration outcomes revealed a nuanced relationship with grape stem amendments, demonstrating non-lethal effects and enhanced reproduction at certain concentrations. However, higher grape stem percentages (E25) revealed a slight delay in regeneration. Grape stem exposure induced changes in antioxidant enzyme activities, particularly in detoxification mechanisms mediated by GST and POD, with distinct activity levels observed in blastema and adjacent tissues. Grape stems as soil amendments demonstrate potential benefits for earthworm health, including improved reproduction and modulated oxidative stress responses. However, optimal application rates are crucial to avoid adverse effects on regeneration. These findings highlight the dual role of soil amendments in nutrient provision and promoting the well-being of soil organisms. Graphical Abstract

Dynamics and interrelationships between antibiotic resistance, organic micropollutants and bacterial communities in full-scale rural constructed wetlands - A. Margarida Teixeira; Diana Matos; Norberta Coelho; Lahiruni M. Halwatura; Ivone Vaz-Moreira; Paula M.L. Castro; Diana S. Aga; Célia M. Manaia (Journal of Cleaner Production, 2025)

Coconut shell derived activated carbon for effective separation of greenhouse gases - Julio E. Sosa; Rui.P.P.L. Ribeiro; Inês Matos; Maria Bernardo; Isabel M. Fonseca; José P.B. Mota; João M.M. Araújo; Ana B. Pereiro (International Journal of Refrigeration, 2025)

Mathematical modeling of multicomponent extraction of metal ions by polymer membranes - M. B. de Vilhena; B. C. de Matos Junior; J. L. Ferreira; S. de A. Cardoso; B. M. Viegas; J. N. N. Quaresma; J. A. da S. Souza; E. N. Macêdo (International Journal of Environmental Science and Technology, 2025)

Observations of Sargassum carbon influx and biogeochemical impact in La Parguera Marine Reserve - Priscilla N. Molina-Cora; Julio M. Morell; Loraine Martell-Bonet; Luis R. Rodriguez-Matos; Julián E. Morell; Maribel Vélez-Rivera (Frontiers in Marine Science, 2025)
The massive influx of pelagic Sargassum spp. species, also known as Sargassum inundation events (SIEs), first arrived at the Caribbean’s coastal waters in 2011. These events have been linked to hypoxia, among other ecological disturbances. Here, we report data from 2022 on (1) an assessment of the relative magnitude of particulate organic carbon (POC) load arising from SIEs into the La Parguera Marine Reserve (LPMR) basin off the southwest coast of Puerto Rico and (2) the biogeochemical impact of SIE in a nearshore mangrove key within the reserve, Monsio Jose Key Bay (MJKB). Our analysis yields that the carbon influx increased by 20% in the LPMR basin and by 103% in MJKB. Weekly observations of Sargassum input, along with the collection and analysis of water samples in MJKB, evidenced a cause-effect relation between Sargassum carbon loading and frequency of hypoxic (DO < 2 mg·L -1 ) and critically acidic conditions (Aragonite saturation, Ω < 2.0). During the 2022 Sargassum season, hypoxic conditions were detected in 43% of samples collected in MJKB. Considering the modulation of biogeochemical parameters by changes in tide height (Δh) and wind speed (m·s -1 ), stepwise multiple regression analyses (RDA-AIC model selection) showed that significant parameters influencing DO, pH, and Ω include the Sargassum carbon influx and Δh ( p < 0.05). These findings strongly support the hypothesis that the additional input of POC influx enhances microbial mineralization rates responsible for depressed oxygen concentrations and acidic conditions, which could be detrimental to coastal ecosystems. This is particularly concerning in areas prone to SIEs where geomorphological features facilitate the entrainment of floating materials. Proper management requires the identification of vulnerable sites and Sargassum removal. Ongoing efforts towards that goal are underway for LPMR.

Neurological lesions in cervids: A study in Portugal - M.A. Pires; J. Macêdo; F. Seixas; A. Gama; M. de Lurdes Pinto; A. Alves; I. Pires; A. Cristina Matos; L. Figueira; C. Lima; P. Mendonça; P. Carvalho; et al. (Journal of Comparative Pathology, 2025)

Enhancing commercial SOFCs fed directly with ethanol through a modified manganite coating - F. Matos de Oliveira; S. Vecino-Mantilla; Z. Hafsi; M.V. Barp; F. D’Acapito; A. Puri; J. Perez; E. Ticianelli; M. Lo Faro (Chemical Engineering Journal, 2025)

Corrigendum to “Synthesis of controlled size starch nanoparticles (SNPs) title of article” [Carbohydr. Polym. 250 (2020) 116938] - G. Gutiérrez; D. Morán; A. Marefati; J. Purhagen; M. Rayner; M. Matos (Carbohydrate Polymers, 2025)

Multi-biomarker analysis of sub-chronic PAH mixture effects in fish at environmentally relevant levels - B. Matos; I. Bramatti; C.D. Santos; V. Branco; M. Martins (Aquatic Toxicology, 2025)

Anthropogenic intensification on plant-pollinator interactions over four decades in Chile: a spatiotemporal assessment - Bárbara Matos da Cunha Guimarães; Rafaela Cabral Marinho; Gastón O. Carvallo; Pietro K. Maruyama; Maureen M. Murúa; André Rodrigo Rech; Lorena Vieli; Paulo E. Oliveira; Francisco E. Fontúrbel (Regional Environmental Change, 2025)

Insights into the thermal stability properties of two hardwoods from the Amazon rainforest - L. de Souza-Cavalcante; F. Guerrero; J. Anglada-Rivera; Y. Leyet; F. M. A. da Silva; G. Q. Ramos; R. Matos; H. D. da Fonseca Filho (Journal of the Indian Academy of Wood Science, 2025)

Do (xeno)estrogens pose a risk to earthworms? Soy isoflavones and estradiol impact gonad structure and induce oxidative stress in Eisenia fetida - Tiago Azevedo; Rita Silva-Reis; Beatriz Medeiros-Fonseca; Mariana Gonçalves; Gabriel Mendes; Marta Roboredo; Maria J. Rocha; Francisco Peixoto; Maria de Lurdes Pinto; Manuela Matos; João R. Sousa; Paula A. Oliveira; et al. (Chemosphere, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Enhancing Sea Wave Monitoring Through Integrated Pressure Sensors in Smart Marine Cables - Tiago Matos; Joao L. Rocha; Marcos S. Martins; Luis M. Gonçalves (Journal of Marine Science and Engineering, 2025)
The need for real-time and scalable oceanographic monitoring has become crucial for coastal management, marine traffic control and environmental sustainability. This study investigates the integration of sensor technology into marine cables to enable real-time monitoring, focusing on tidal cycles and wave characteristics. A 2000 m cable demonstrator was deployed off the coast of Portugal, featuring three active repeater nodes equipped with pressure sensors at varying depths. The goal was to estimate hourly wave periods using fast Fourier transform and calculate significant wave height via a custom peak detection algorithm. The results showed strong coherence with tidal depth variations, with wave period estimates closely aligning with forecasts. The wave height estimations exhibited a clear relationship with tidal cycles, which demonstrates the system’s sensitivity to coastal hydrodynamics, a factor that numerical models designed for open waters often fail to capture. The study also highlights challenges in deep-water monitoring, such as signal attenuation and the need for high sampling rates. Overall, this research emphasises the scalability of sensor-integrated smart marine cables, offering a transformative opportunity to expand oceanographic monitoring capabilities. The findings open the door for future real-time ocean monitoring systems that can deliver valuable insights for coastal management, environmental monitoring and scientific research.

Moderate to high-severity wildfires: Main restoration strategies applied in Mediterranean ecosystems - Olena Dorosh; Cristina Delerue-Matos; Paula Castro; Manuela M. Moreira (Journal of Environmental Management, 2025)

Metabolic response of Zostera noltei transplants in a historically contaminated ecosystem - V.H. Oliveira; D. Matos; A.I. Sousa; M. Dolbeth; B. Marques; A.I. Lillebø; M.E. Pereira; S. Díez; E. Figueira; J.P. Coelho (Journal of Environmental Management, 2025)

A two-stage probabilistic flexibility management model for aggregated residential buildings - Saeed Akbari; João Martins; Luis M. Camarinha-Matos; Giovanni Petrone (Energy and Buildings, 2025)

Steam reforming for winery wastewater treatment: Hydrogen production and energy self-sufficiency assessment - J. Matos; M.A. Soria; Luis M. Madeira (Biomass and Bioenergy, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Graphene-like biochars from pyrolysis of sugarcane bagasse and exhausted black acacia bark for the production of supercapacitors - Mayara R. Fornari; Bruna M. Hryniewicz; Tassya T.S. Matos; Juliana Schultz; Marcio Vidotti; Antonio S. Mangrich (Biomass and Bioenergy, 2025)

High performance metal-free N/S-doped biochars towards oxygen reduction reaction - Renata Matos; António J.S. Fernandes; Victor K. Abdelkader-Fernández; Andreia F. Peixoto; Diana M. Fernandes (Biomass and Bioenergy, 2025)

Nanolabels for biosensors based on lateral flow immunoassays - C. Saweres-Argüelles; A. Sánchez-Calvo; E. Serrano-Pertierra; M. Matos; M.C. Blanco-López (Analytica Chimica Acta, 2025)

HiDaFernPT : Historical data of spore availability for 121 fern and lycopod taxa in Portugal (1926–2013) - Sérgio Timóteo; Ruben Heleno; Filipe Covelo; Joaquim Santos; Pedro Lopes; António C. Gouveia; Arménio Matos; Agostinho Salgado; M. Teresa Girão da Cruz; João Farminhão; Marta Horta; Guilherme Barreto; et al. (Ecology, 2025)
Species phenology is being altered by ongoing climate changes with yet underappreciated consequences for ecological processes and ecosystem stability. Contrary to what happens with some key life events of flowering plants, comparatively little information exists about fern and lycophyte phenology and how it is affected by the current climatic changes. In part, this stems from the lack of long‐term datasets. Here we provide information on the collection day and site of the spores of 121 native and introduced fern (Polypodiopsida) and lycopod (Lycopodiopsida) taxa for the Index Seminum of the Botanic Garden of the University of Coimbra. Spores were collected from spontaneous and cultivated individuals across Portugal between 1926 and 2013. The database includes 3383 curated records with information on the species, or infraspecific taxa (including authority), and are fully georeferenced and provided with a confidence interval for the collection site. Taxonomy was first curated manually by in‐house botanists and then harmonized according to the Global Biodiversity Information Facility (GBIF) backbone taxonomy. The data are released under a Creative Commons Attribution Non Commercial (CC‐BY‐NC 4.0) license.

Transplantation of seagrass (Zostera noltei) as a potential nature-based solution for the restoration of historically contaminated mudflats - Vítor H. Oliveira; B.A. Fonte; A.I. Sousa; D. Crespo; J.M. Dias; N. Vaz; D. Matos; E. Figueira; M.E. Pereira; A.I. Lillebø; M. Dolbeth; J.P. Coelho (Science of The Total Environment, 2025)

Plasma miRNAs Correlate with Structural Brain and Cardiac Damage in Friedreich’s Ataxia - Thiago M. Peluzzo; André S. Vieira; Alexandre H. B. Matos; Cynthia Silveira; Mariana Martin; Otávio R. C. Filho; Thiago J.R. Rezende; Alberto R. M. Martinez; Marcondes C. França (The Cerebellum, 2024)

Retraction notice to “Cellulose microcrystalline: A promising ecofriendly approach to control Culex quinquefasciatus larvae” [STOTEN 901 (2023) 165952] - Sindoval Silva de Souza; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2024)

Investigating multiple vegetable oils and recycled variant for microplastics extraction from water, integrated with Raman spectroscopy - R. Garzón-Vidueira; D. Rede; R. Rial-Otero; R. Vilarinho; J.A. Moreira; S. Jorge; M. André; R. Barbosa; C. Delerue-Matos; V. Cruz Fernandes (Science of The Total Environment, 2024)

Reaction of two sciaenid species to passing boats: Insights from passive acoustic localisation - André B. Matos; Manuel Vieira; M. Clara P. Amorim; Paulo J. Fonseca (Estuarine, Coastal and Shelf Science, 2024)

Diversity and potential functional role of phyllosphere-associated actinomycetota isolated from cupuassu (Theobroma grandiflorum) leaves: implications for ecosystem dynamics and plant defense strategies - Jéssica Pereira de Matos; Dilson Fagundes Ribeiro; Ana Karla da Silva; Camila Henriques de Paula; Isabella Ferreira Cordeiro; Camila Gracyelle de Carvalho Lemes; Angélica Bianchini Sanchez; Lorrana Cachuite Mendes Rocha; Camila Carrião Machado Garcia; Nalvo F. Almeida; Rafael Moyses Alves; Vinicius A. C. de Abreu; et al. (Molecular Genetics and Genomics, 2024)

Prospecting for New Potential Biocontrol Agents Against Colletotrichum lindemuthianum, the Causal Agent of Bean Anthracnose - Rosilene C. Matos; Sibele A. da Silva; Isabella F. Cordeiro; Angélica B. Sanchez; Maria R. A. Damasceno; Lorrana C. M. Rocha; Gustavo S. Kajitani; Josino José Barbosa; Marisa V. de Queiroz; Camila Carrião Machado Garcia; Leandro M. Moreira (Journal of Soil Science and Plant Nutrition, 2024)

Unsupervised segmentation for sandstone thin section image analysis - Rayan T. C. M. Barbosa; E. L. Faria; Matheus Klatt; Thais C. Silva; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2024)

Supplementation with 25-hydroxicolecalciferol increases the nutritional efficiency and carcass growth of grazing Nellore young bulls - Fernanda S. Mudado; Melissa B. Silveira; Henrique J. Fernandes; Alexandre Perdigão; Diego M.M. dos Santos; Thomas H.R. da Silva; Jarbas M. da Silva Júnior; Isabelle E. de Matos; Victor V. de Carvalho; Tiago S. Acedo; Aline G. da Silva (Animal Feed Science and Technology, 2024)

Leaf architecture and functional traits for 122 species at the University of California Botanical Garden at Berkeley - Ilaine Silveira Matos; Mickey Boakye; Monica Antonio; Sonoma Carlos; Ashley Chu; Miguel A. Duarte; Andrea Echevarria; Adrian Fontao; Lisa Garcia; LeeAnn Huang; Breanna Carrillo Johnson; Shama Joshi; et al. (Ecology, 2024)
The dataset contains leaf venation architecture and functional traits for a phylogenetically diverse set of 122 plant species (including ferns, basal angiosperms, monocots, basal eudicots, asterids, and rosids) collected from the living collections of the University of California Botanical Garden at Berkeley (37.87° N, 122.23° W; CA, USA) from February to September 2021. The sampled species originated from all continents, except Antarctica, and are distributed in different growth forms (aquatic, herb, climbing, tree, shrub). The functional dataset comprises 31 traits (mechanical, hydraulic, anatomical, physiological, economical, and chemical) and describes six main leaf functional axes (hydraulic conductance, resistance and resilience to damages caused by drought and herbivory, mechanical support, and construction cost). It also describes how architecture features vary across venation networks. Our trait dataset is suitable for (1) functional and architectural characterization of plant species; (2) identification of venation architecture‐function trade‐offs; (3) investigation of evolutionary trends in leaf venation networks; and (4) mechanistic modeling of leaf function. Data are made available under the Open Data Commons Attribution License.

Antidepressants and COVID-19: Increased use, occurrence in water and effects and consequences on aquatic environment. A review - Antón Puga; Manuela M. Moreira; M. Angeles Sanromán; Marta M. Pazos; Cristina Delerue-Matos (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Effect of lactose on the in vitro development of sheep secondary follicles - Kíscyla O. Andrade; Alane P.O. Monte; Regina L.S. Silva; Ricássio S. Barberino; Istefani M. Mota; Gabriela C.S. Santos; Valéria S. Guimarães; Gizele A.L. Silva; Claudener S. Teixeira; Maria Helena T. Matos (Animal Reproduction Science, 2024)

Influence of Dolphin-Watching Tourism Vessels on the Whistle Emission Pattern of Common Dolphins and Bottlenose Dolphins - Ana A. Silva; Joana Castro; André Cid; Sérgio M. Jesus; Fábio L. Matos (Oceans, 2024)
Recent years have seen a notable rise in dolphin-watching boat activities along the Algarve coast in Portugal, potentially affecting the common dolphin (Delphinus delphis) and bottlenose dolphin (Tursiops truncatus) local populations. This study examines the impact of increasing underwater noise levels from these boats on dolphin vocalizations. Field recordings were conducted from June to September 2022, analyzing dolphin whistles in various boat presence scenarios. The results indicate significant changes in whistle-frequency characteristics with boat presence, including increased start, low, and high frequencies, alongside a decrease in the number of inflection points in modulated whistles. The changes might negatively impact dolphin populations viability, underscoring the need for further research. Additionally, improved mitigation strategies may be necessary to reduce the potential negative effects of dolphin watching on cetacean communication and behavior in the Algarve region.

Influence of paternal factors on plastic ingestion and brominated chemical exposure in East Tropical Atlantic Procellariid chicks - Diana M. Matos; J.A. Ramos; A.L.C. Brandão; Francisca Baptista; Isabel Rodrigues; J.O. Fernandes; L.A.E. Batista de Carvalho; M.P.M. Marques; S.C. Cunha; Stefan Antunes; V.H. Paiva (Science of The Total Environment, 2024)

Disseminated paracoccidioidomycosis in a captive western black-handed tamarin (Saguinus niger) - Isabelle D. de Oliveira; Eduardo Ferreira-Machado; Jamile M. Garcia; Sarah R.J.S. Simões; Ketlyn B. Figueiredo; Rodrigo A. Ressio; André L.M. da Costa; Flora N. Matos; Cássia R.R. Gonzaga; Shamira S. Leandro; Marina A. de Medeiros; Rodrigo H.F. Teixeira; et al. (Journal of Comparative Pathology, 2024)

Portuguese macroalgae and halophytes for human consumption: Minimal risk of norovirus and Salmonella infection - Joana M. Oliveira; Miguel A. Pardal; Leonel Pereira; Ana M. Matos; Elsa T. Rodrigues (Food Control, 2024)

SARS-CoV2 Nsp1 is a metal-dependent DNA and RNA endonuclease - Bruno A. Salgueiro; Margarida Saramago; Mark D. Tully; Federico Issoglio; Sara T. N. Silva; Ana C. F. Paiva; Cecília M. Arraiano; Pedro M. Matias; Rute G. Matos; Elin Moe; Célia V. Romão (BioMetals, 2024)
Over recent years, we have been living under a pandemic, caused by the rapid spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). One of the major virulence factors of Coronaviruses is the Non-structural protein 1 (Nsp1), known to suppress the host cells protein translation machinery, allowing the virus to produce its own proteins, propagate and invade new cells. To unveil the molecular mechanisms of SARS-CoV2 Nsp1, we have addressed its biochemical and biophysical properties in the presence of calcium, magnesium and manganese. Our findings indicate that the protein in solution is a monomer and binds to both manganese and calcium, with high affinity. Surprisingly, our results show that SARS-CoV2 Nsp1 alone displays metal-dependent endonucleolytic activity towards both RNA and DNA, regardless of the presence of host ribosome. These results show Nsp1 as new nuclease within the coronavirus family. Furthermore, the Nsp1 double variant R124A/K125A presents no nuclease activity for RNA, although it retains activity for DNA, suggesting distinct binding sites for DNA and RNA. Thus, we present for the first time, evidence that the activities of Nsp1 are modulated by the presence of different metals, which are proposed to play an important role during viral infection. This research contributes significantly to our understanding of the mechanisms of action of Coronaviruses.

Soil carbon stock changes in a crop-livestock-forestry integration in Southern Goiás State, Brazil - B. E. Madari; P. S. Matos; J. M. Oliveira; M. T. M. Carvalho; A. L. R. Silveira; P. L. O. A. Machado; W. A. Araujo; M. M. B. Siqueira; T. M. Ferraresi; F. M. C. Freitas; P. V. Rizzo; R. R. Silva; et al. (Agroforestry Systems, 2024)

Exploring the potential of biomass-derived carbons for the separation of fluorinated gases with high global warming potential - Julio E. Sosa; Rui P.P.L. Ribeiro; Inês Matos; Maria Bernardo; Isabel M. Fonseca; José P.B. Mota; João M.M. Araújo; Ana B. Pereiro (Biomass and Bioenergy, 2024)

Do endocrine disrupting compounds impact earthworms? A comprehensive evidence review - Tiago Azevedo; Mariana Gonçalves; Rita Silva-Reis; Beatriz Medeiros-Fonseca; Marta Roboredo; João R. Sousa; Paula A. Oliveira; Maria de Lurdes Pinto; Francisco Peixoto; Isabel Gaivão; Manuela Matos; Ana M. Coimbra (Reviews in Environmental Science and Bio/Technology, 2024)
Endocrine-disrupting compounds (EDCs) are ubiquitous in soil, posing serious risks to soil biota, especially earthworms, which have been found to be affected by these compounds, despite not being their typical target organisms. Earthworms are essential for sustaining soil health and quality, by promoting soil aeration, organic matter decomposition and nutrient cycling, among other functions. This review synthesizes available literature evidencing the negative impact of EDC exposure, through traditional endocrine pathways and other toxicological mechanisms, on histopathological, biochemical, molecular and reproductive endpoints of earthworms. The compounds described, in the consulted literature, to induce histopathological, biochemical, genotoxicity and molecular and reproductive alterations include antibiotics, antimicrobial additives, flame retardants, fragrances, fungicides, herbicides, hormones, inorganic ions, insecticides, organic UV filters, parabens, perfluoroalkyl substances, pesticides, petroleum derivatives, plasticizers and polychlorinated biphenyls. These compounds reach soil through direct application or via contaminated organic amendments and water derived from potentially polluted sources. The findings gather in the present review highlight the vulnerability of earthworms to a broad spectrum of chemicals with endocrine disrupting capacity. Additionally, these studies emphasize the physiological disruptions caused by EDC exposure, underscoring the critical need to protect biodiversity, including earthworms, to ensure soil quality and ecosystem sustainability. Ongoing research has provided insights into molecular mechanisms responsive to EDCs in earthworms, including the identification of putative hormone receptors that exhibit functional similarity to those present in vertebrates. In conclusion, this review emphasizes the impact of EDCs in earthworms, especially through non-hormonal mediated pathways, and addresses the need for strong regulatory frameworks to mitigate the detrimental effects of EDCs on soil invertebrates in order to safeguard soil ecosystems. Graphical abstract

Novel 3D electro-Fenton reactor based on a catalytic packed bed reactor of perovskite/carbon microelectrodes for the removal of carbamazepine in wastewater - A. Cruz del Álamo; A. Puga; C.M. Dias Soares; M.I. Pariente; M. Pazos; R. Molina; M.A. Sanromán; F. Martínez; C. Delerue-Matos (Journal of Environmental Chemical Engineering, 2024)

Correction to: The net-tube caddisflies (Trichoptera: Psychomyioidea: Xiphocentronidae) from the Brazilian Amazon: discovery of new species and reports of new distributional records - Gleison R. Desidério; Albane Vilarino; Laissa S. Santos; Marcos A. R. Pires; Ana M. Pes; Talissa Matos; Karina Dias-Silva; Neusa Hamada (Biologia, 2024)

Efficient carbamazepine removal from wastewater using a continuous three-dimensional electro-Fenton system at natural pH - Antón Puga; Cristina Soares; Ana Cruz del Álamo; M. Isabel Pariente; Raúl Molina; Fernando Martínez; M. Angeles Sanromán; Marta M. Pazos; Cristina Delerue-Matos (Journal of Water Process Engineering, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

The net-tube caddisflies (Trichoptera: Psychomyioidea: Xiphocentronidae) from the Brazilian Amazon: discovery of new species and reports of new distributional records - Gleison R. Desidério; Albane Vilarino; Laissa S. Santos; Marcos A. R. Pires; Ana M. Pes; Talissa Matos; Karina Dias-Silva; Neusa Hamada (Biologia, 2024)

Transcriptome profiling of the posterior salivary glands of the cuttlefish Sepia officinalis from the Portuguese West coast - Cátia Gonçalves; Inês Moutinho Cabral; António P. Alves de Matos; Ana R. Grosso; Pedro M. Costa (Frontiers in Marine Science, 2024)
Cephalopods like octopuses and cuttlefishes are known to secrete a ‘toxic saliva’ to inject into their prey, especially crustaceans since the XIX century. However, only in the mid-XX century were the first coleoid-specific toxins successfully isolated. Motivated by the growing interest on the global ocean as an almost inexhaustible source of novel bioactive compounds, we used RNA-Seq – based transcriptomics and de novo assembly of transcriptomes to screen the posterior salivary glands of Sepia officinalis (the common cuttlefish) from the Portuguese West coast for toxins and other bioactive proteins and peptides. Supported by microanatomical analyses, the posterior salivary glands constitute indeed the ‘venom gland’ whereas the more elusive anterior salivary glands (embedded in the buccal mass) are responsible for the production of mucin-rich saliva that is effectively the vehicle that transports the toxins as the venom is injected into the prey. Indeed, the transcriptomic profiling suggests that the cuttlefish venom is complex mixture of bioactive proteins, among which neurotoxins are major players, together with enzymes whose function is to digest the extracellular matrix to facilitate diffusion of the toxins. Nonetheless, by comparing with previous RNA-Seq data obtained from S. officinalis collected from other biogeographical areas, it may be suggested that significant inter-populational variation in venom composition can occur, which may potentially increase the span of bioactives secreted by these animals. We isolated and validated the full coding sequences for three important toxins, a cysteine-rich venom protein (CRVP), a venom insulin (VIns) and a cephalotoxin (CTX). The toxins seem to be relatively conserved among coleoids but diverging from other venomous mollusks such as cone snails. Their properties as potent modulators of glucose (in the case of VIns) and as potential neurotoxins (like CRVP and CTX) can render them primer targets for drug development.

Comparison between commercial media and TRIS-egg yolk extender in the refrigerated storage of collared peccary semen at 17 °C - Romário P. Santos; Samara S.J. Moreira; Luana G.P. Bezerra; Yasmim C.S. Cavalcante; Ana G. Pereira; Tayná M. Matos; Moacir F. Oliveira; Alexandre R. Silva (Animal Reproduction Science, 2024)

An empirical DNA-based identification of morphologically similar snappers (Lutjanus campechanus, Lutjanus purpureus) using a versatile bioinformatics workflow for the discovery and analysis of informative single-nucleotide polymorphisms - Robert A. Literman; Mayara P. V. Matos; Sara M. Handy; Jonathan R. Deeds (Frontiers in Marine Science, 2024)
The commercially important species Lutjanus campechanus (Northern/Gulf red snapper) and Lutjanus purpureus (Southern/Caribbean red snapper) are the protagonists of a decade’s long taxonomic debate over their species delimitation, due in part to partial habitat overlap, extensive morphological similarity, and the lack of resolution when applying canonically reliable DNA barcoding approaches. In this study, we leveraged publicly available RAD-Seq data for L. campechanus and L. purpureus to identify species-informative single‐nucleotide polymorphisms (SNPs) at the genome scale that were successful in distinguishing the Northern and Southern red snappers, while also detecting individuals exhibiting introgression. This 4-step empirical approach demonstrates the value of applying novel bioinformatics pipelines to existing genome-scale data to maximize the distillation of informative subsets. Our results facilitate economically relevant species identification in addition to confirming or challenging species identifications for specimens with data in public databases. These findings and their applications will benefit future sustainability strategies and broader research questions surrounding these overfished and evolutionarily entangled snapper species.

Decision-making based on sustainability analysis using GREENSCOPE - Ricardo N. Dias; Rui M. Filipe; Henrique A. Matos (Clean Technologies and Environmental Policy, 2024)
Current economic and environmental pressure encourages companies to invest and reform processes in a sustainable way. However, the decision on the best sustainable investment in a given industry may not be as straightforward as given by the independent economic and environmental indicators. Analyzing such indicators for investment in process alternatives is a complex multi-objective decision-making process. Many methods can help solve multi-objective problems, GREENSCOPE suggests using the Addictive Utility Method, which may have some shortcomings. In this work, the Analytic Hierarchy Process and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) are applied to the indicator scores obtained with the GREENSCOPE methodology. The Analytical Hierarchy Process is applied with Marginal Rate of Substitution, to obtain the priority matrices. MATLAB was used to apply the methods and through an algorithm, to determine the adequate number of indicators to be used. Three cases were studied, namely a biorefinery plant, and two academic case studies on the production of acetaldehyde from ethanol and propylene glycol from glycerol. The two academic cases were modeled in Aspen Plus, to obtain process data, and linked to GREENSCOPE using MATLAB. The methodology was applied to some proposed alternatives where the sustainability improvement of energy integration and material recycling was tested. The new methodology was able to identify the more sustainable case among the alternatives. This methodology based on TOPSIS proved to be the best choice, avoiding the weighting of indicators, and providing an expected analytical decision among alternatives. Graphical abstract

The decline and death of Canary Island date palms in México City is associated with subgroup 16SrIV-D phytoplasmas - C. F. Ortiz-García; D. Alvarado-Rosales; C. Oropeza; L. de L. Saavedra-Romero; S. Aranda-Ocampo; A. Almaraz-Sánchez; A. Quezada-Salinas; A. Equihua-Martínez; S. E. García-Díaz; M. Narváez; G. Nic-Matos; P. J. Palma-Cancino; et al. (Australasian Plant Pathology, 2024)

Recovery of rare earth elements (Nd3+ and Dy3+) by using carbon-based adsorbents from spent tire rubber - M. Nogueira; I. Matos; M. Bernardo; L.A.C. Tarelho; A.M. Ferraria; A.M. Botelho do Rego; I. Fonseca; N. Lapa (Waste Management, 2024)

Microplastics ingestion and endocrine disrupting chemicals (EDCs) by breeding seabirds in the east tropical Atlantic: Associations with trophic and foraging proxies (δ15N and δ13C) - Diana M. Matos; J.A. Ramos; A.L.C. Brandão; Alexandra Baeta; Isabel Rodrigues; I. dos Santos; João Coentro; J.O. Fernandes; L.A.E. Batista de Carvalho; M.P.M. Marques; S.C. Cunha; S.H. Santos; et al. (Science of The Total Environment, 2024)

Hypertrophic cardiomyopathy in a dog: a systematic diagnostic approach - J. Novo Matos; J. Silva; S. Regada; S. Rizzo; M. Serena Beato; C. Basso (Journal of Veterinary Cardiology, 2024)

Comparative responses and effects of exposure to metallic and nanoparticle zinc in the mussel Mytilus galloprovincialis - Joana Roma; Madalena Missionário; Carolina Madeira; Ana Rita Matos; Catarina Vinagre; Pedro M. Costa; Bernardo Duarte (Estuarine, Coastal and Shelf Science, 2024)

Toxicity of carbon nanofibers in earthworms (Lumbricus terrestris) naturally infected with Monocystis sp. - Mateus Flores Montalvão; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2024)

Enhancing the taxonomic delimitation of Lippia origanoides Kunth (Verbenaceae) by analyzing volatile terpenes and molecular markers in micropropagated accessions - Laís M. Frattini; Arthur A. Oliveira; Jhoão S. Kotsubo; Íris B. Gorne; Isabel C. Silva; Jober C. E. Freitas; Cristiano F. Resende; Ana C. Mezzonato-Pires; Elyabe M. Matos; Juliana M. L. Lopes; Lyderson F. Viccini; Richard M. Grazul; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Sustainability analysis of a solar-driven calcium looping plant for thermochemical energy storage - Ricardo N. Dias; Rui M. Filipe; Henrique A. Matos (Journal of Cleaner Production, 2023)

An improved reference genome and first organelle genomes of Quercus suber - Ana Usié; Octávio Serra; Pedro M. Barros; Pedro Barbosa; Célia Leão; Tiago Capote; Tânia Almeida; Leandra Rodrigues; Isabel Carrasquinho; Joana B. Guimarães; Diogo Mendoça; Filomena Nóbrega; et al. (Tree Genetics & Genomes, 2023)
Cork oak ( Quercus suber L.) is an ecologically and economically important evergreen tree species native to the Mediterranean region and widespread in southwest Europe and northwest Africa. An improved genome assembly of cork oak using a combination of Illumina and PacBio sequencing is presented in this study. The assembled genome contains 2351 scaffolds longer than 1000 bp, accounting for 765.7 Mbp of genome size, L90 of 755, and a N50 of 1.0 Mbp, with 40,131 annotated genes. The repetitive sequences constitute 53.6% of the genome. The genome sequences of chloroplast and mitochondrion were determined for the first time, with a genome size of 161,179 bp and 531,858 bp, respectively. Phylogenetic analysis based on complete chloroplast genome sequence showed that Q. suber is closely related to Quercus variabilis , two cork-producing species with commercial use. All data generated are available through the public databases, being ready to be used without restrictions. This study provides an improved nuclear genome assembly together with the organelle genomes of cork oak. These resources will be useful for further breeding strategies and conservation programs and for comparative genomic studies in oak species.

Haplotype diversity patterns in Quercus suber (Fagaceae) inferred from cpDNA sequence data - Filipe Sousa; Mariana Bray Viegas; Joana Costa; Isabel Marques; Francisco Pina-Martins; Fernanda Simões; José Matos; Maria Glushkova; Célia Miguel; Maria Manuela Veloso; M. Margarida Oliveira; Cândido Pinto Ricardo; et al. (Plant Systematics and Evolution, 2023)
Chloroplast genome diversity in cork oak ( Quercus suber ) is characterised by the occurrence of haplotypes that are akin to those found in other Mediterranean oak species, particularly in Q. ilex and Q. rotundifolia , suggesting the possible presence of an introgressed chloroplast lineage. To further investigate this pattern, we reconstructed chloroplast haplotypes by sequencing four chloroplast markers (cpDNA), sampled across 181 individuals and 10 taxa. Our analyses resulted in the identification of two diversified chloroplast haplogroups in Q. suber , corresponding to a geographically widespread lineage and an Afro-Iberian lineage. Time-calibrated phylogenetic analyses of cpDNA point to a Miocene origin of the two haplogroups in Q. suber , suggesting that the Afro-Iberian lineage was present in cork oak before the onset of glaciation periods. The persistence of the two haplogroups in the western part of the species distribution range may be a consequence of either ancient introgression events or chloroplast lineage sorting, combined with different fixation in refugia through glaciation periods. Our results provide a comprehensive insight on the origins of chloroplast diversity in these ecologically and economically important Mediterranean oaks.

RETRACTED: Cellulose microcrystalline: A promising ecofriendly approach to control Culex quinquefasciatus larvae - Sindoval Silva de Souza; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2023)

Ethylene photocatalytic degradation using TiO2 immobilized in a NETmix mili-photoreactor - Jéssica de Matos Fonseca; Sandra M. Miranda; Joana P. Monteiro; Regina de Fátima Peralta Muniz Moreira; Germán Ayala Valencia; Alcilene Rodrigues Monteiro; Vítor J.P. Vilar (Journal of Environmental Chemical Engineering, 2023)

P23-05: Urinary monohydroxyl-polycyclic aromatic hydrocarbons and metals in firefighters with active participation in controlled structure fires - J. Teixeira; R. Azevedo; A. Almeida; F. Rodrigues; A. Santos-Silva; C. Delerue-Matos; M. Oliveira (Toxicology Letters, 2023)

P16-13: A step forward the in vitro toxicity assessment of firefighters’ exposure to controlled fires in human cell culture models - M.J. Bessa; J. Teixeira; C. Delerue-Matos; B. Sarmento; M. Oliveira; F. Rodrigues (Toxicology Letters, 2023)

Development of waste-to-energy through integrated sustainable waste management: the case of ABREN WtERT Brazil towards changing status quo in Brazil - Yuri Schmitke Almeida Belchior Tisi; Flavio Arantes Matos; Maria Luisa N. M. Carneiro (Waste Disposal & Sustainable Energy, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Nano-zero-valent particles synthesized with agroindustry wastes for pesticide degradation under real conditions - Aida M. Díez; Virgínia Cruz Fernandes; Manuela M. Moreira; M. Pazos; M.A. Sanromán; T. Albergaria; C. Delerue-Matos (Process Safety and Environmental Protection, 2023)

Hybrid Decentralized Systems of Non-potable Water Supply: Performance and Effectiveness Analysis - A Ferreira; C. Santos; M. A. Imteaz; C. Matos (Water Resources Management, 2023)
This article presents a study of Hybrid Rainwater/Greywater Systems (HRGS), with the objective of perceiving the main factors that influence their performance and how they can be optimized. For this goal, a decision support tool, that makes their dimensioning and performs an economic and performance analysis, was used for four different types of buildings: a single-family house, a multifamily building and two service buildings. For each case, distinct scenarios were defined, considering different end-uses of non-potable water, in order to evaluate the performance of the systems using effectiveness and performance indicators. Results show that the effectiveness of “non-potable water consumption” is influenced by two main factors: the final uses considered for non-potable water and the storage volume. In most of the study cases, values of effectiveness (ratio between the volume of non-potable water used and non-potable water demand for the final uses considered) greater than 50% were obtained. In the case of domestic buildings, such as single-family house and multifamily building effectiveness values above 67%, were obtained. And for the case of service buildings, the effectiveness was between 42.8 and 65.6% in one case, and between 12.9 and 93.6% for the other. The best performance of the studied hybrid systems is achieved when the volume of non-potable water used in the building is maximized, resulting in greater savings of potable water. In addition, the larger the fraction of greywater reused, the lower the volume of wastewater produced and sent directly to the sanitation network.

Proteostasis networks in aging: novel insights from text-mining approaches - Diogo Neves; Sara Duarte-Pereira; Sérgio Matos; Raquel M. Silva (Biogerontology, 2023)
Aging is a topic of paramount importance in an increasingly elderly society and has been the focus of extensive research. Protein homeostasis (proteostasis) decline is a hallmark in aging and several age-related diseases, but which specific proteins and mechanisms are involved in proteostasis (de)regulation during the aging process remain largely unknown. Here, we used different text-mining tools complemented with protein–protein interaction data to address this complex topic. Analysis of the integrated protein interaction networks identified novel proteins and pathways associated to proteostasis mechanisms and aging or age-related disorders, indicating that this approach is useful to identify previously unknown links and for retrieving information of potential novel biomarkers or therapeutic targets.

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Ventricular pre-excitation in cats: 17 cases - M. Sidler; G. Santarelli; A. Kovacevic; J. Novo Matos; N. Schreiber; M. Baron Toaldo (Journal of Veterinary Cardiology, 2023)

Magnetic solid phase extraction as a nonchromatographic method for the quantification of ultratrace inorganic arsenic in rice by inductively coupled plasma-optical emission spectrometry (ICP OES) - Francisco L.F. da Silva; Francisco E.H. Lima; Davino M. Andrade Neto; Fernando L. de Menezes; Lillian M.U.D. Fechine; Abdullah Akhdhar; Livia P.D. Ribeiro; Ana R.A. Nogueira; Pierre B.A. Fechine; Gisele S. Lopes; Wladiana O. Matos (Food Chemistry, 2023)

In-vitro gastrointestinal digestion of functional cookies enriched with chestnut shells extract: Effects on phenolic composition, bioaccessibility, bioactivity, and α-amylase inhibition - Diana Pinto; Manuela M. Moreira; Jaroslava Švarc-Gajić; Anna Vallverdú-Queralt; Tanja Brezo-Borjan; Cristina Delerue-Matos; Francisca Rodrigues (Food Bioscience, 2023)

DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management - Ana Rita Carreiro; Jaime A. Ramos; Vanessa A. Mata; Nathalie M. Almeida; Isabel Rodrigues; Ivo dos Santos; Diana M. Matos; Pedro M. Araújo; Teresa Militão; Jacob González-Sólis; Vitor H. Paiva; Ricardo Jorge Lopes (Marine Environmental Research, 2023)

The phylogenomics and evolutionary dynamics of the organellar genomes in carnivorous Utricularia and Genlisea species (Lentibulariaceae) - Saura R. Silva; Vitor F.O. Miranda; Todd P. Michael; Bartosz J. Płachno; Ramon G. Matos; Lubomir Adamec; Sergei L.K. Pond; Alexander G. Lucaci; Daniel G. Pinheiro; Alessandro M. Varani (Molecular Phylogenetics and Evolution, 2023)

Impact of anthropogenic noise on the survival and development of meagre (Argyrosomus regius) early life stages - Rita Trabulo; M. Clara P. Amorim; Paulo J. Fonseca; Manuel Vieira; André B. Matos; Thibaut Marin-Cudraz; Marco F.L. Lemos; Ariana B. Moutinho; Sara C. Novais; Pedro Pousão-Ferreira; Ana Candeias-Mendes; Ana M. Faria (Marine Environmental Research, 2023)

Assessment of Habitat Suitability for Common Cockles in the Ria the Aveiro Lagoon Under Average and Projected Environmental Conditions - Fábio L. Matos; Nuno Vaz; Ana Picado; João M. Dias; Francisco Maia; Miguel B. Gaspar; Luísa Magalhães (Estuaries and Coasts, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Lithology identification in carbonate thin section images of the Brazilian pre-salt reservoirs by the computational vision and deep learning - E. L. Faria; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; Willian A. Trevizan; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2022)

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Treatment of Wastewater Containing New and Non-biodegradable Textile Dyes: Efficacy of Combined Advanced Oxidation and Adsorption Processes - Ana J. Feuzer-Matos; Renan C. Testolin; Wendell Pimentel-Almeida; Ramaiana Radetski-Silva; Maria J. Deomar-Simões; Letícia Poyer-Radetski; Rafael Ariente-Neto; Marina J. Batista-Barwinski; Cleder A. Somensi; Claudemir M. Radetski (Water, Air, & Soil Pollution, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Foraging costs drive within-colony spatial segregation in shearwaters from two contrasting environments in the North Atlantic Ocean - Jorge M. Pereira; Jaime A. Ramos; Nathalie Almeida; Pedro M. Araújo; Filipe R. Ceia; Pedro Geraldes; Ana M. Marques; Diana M. Matos; Isabel Rodrigues; Ivo dos Santos; Vitor H. Paiva (Oecologia, 2022)

Latent effects of intertidal encapsulated development on juvenile fitness of the marine snail Acanthina monodon - L. P. Salas-Yanquin; N. P. Pinilla; A. S. Matos; J. A. Bűchner-Miranda; J. M. Navarro; V. M. Cubillos; J. A. Pechenik; O. R. Chaparro (Marine Biology, 2022)

Transcriptome analysis reveals key defense-related genes upon SA induction in Cocos nucifera L. - C. Silverio-Gómez; J. Vega-Arreguín; G. Nic-Matos; M. Narváez-Cab; L. Sáenz-Carbonell; C. Oropeza (Genes & Genomics, 2022)

Production and bioaccessibility of Emiliania huxleyi biomass and bioactivity of its aqueous and ethanolic extracts - B. Vicente; J. Matos; R. Gomes; M. Sapatinha; Cláudia Afonso; T. Rodrigues; A. Amorim; N. M. Bandarra; Carlos Cardoso (Journal of Applied Phycology, 2021)

Using textile industrial sludge, sewage wastewater, and sewage sludge as inoculum to degrade recalcitrant textile dyes in a co-composting process: an assessment of biodegradation efficiency and compost phytotoxicity - Renan C. Testolin; Ana Júlia Feuzer-Matos; Sylvie Cotelle; Fabrizio Adani; Leandro Janke; Gabriel Poyer-Radetski; Antonio C. Pereira; Rafael Ariente-Neto; Cleder A. Somensi; Claudemir M. Radetski (Environmental Science and Pollution Research, 2021)

Distinctive seed dispersal and seed bank patterns of invasive African grasses favour their invasion in a neotropical savanna - Rafael O. Xavier; Alexander V. Christianini; Gabriela Pegler; Marcelo Boccia Leite; Dalva M. Silva-Matos (Oecologia, 2021)

Improved 4-nitrophenol removal at Ti/RuO2–Sb2O4–TiO2 laser-made anodes - Aline R. Dória; Géssica O. S. Santos; Mariane M. S. Pelegrinelli; Deyvid C. Silva; Danielle B. de Matos; Eliane Bezerra Cavalcanti; Ronaldo S. Silva; Giancarlo R. Salazar-Banda; Katlin I. B. Eguiluz (Environmental Science and Pollution Research, 2021)

Evaluation of chelating and cytoprotective activity of vanillin against the toxic action of mercuric chloride as an alternative for phytoremediation - Joelma P. da Silva; Maria do S. Costa; Fabia F. Campina; Camila F. Bezerra; Thiago S. de Freitas; Amanda K. Sousa; Celestina E. Sobral Souza; Yedda M. L. S. de Matos; Francisco N. Pereira-Junior; Irwim R. A. Menezes; Henrique D. M. Coutinho; Janaína E. Rocha (Environmental Geochemistry and Health, 2021)

Effect of rhizome exposure to contrasting abiotic conditions on the performance of the invasive macrophyte Hedychium coronarium J. Koenig (Zingiberaceae) - Amanda Maria Pinheiro; Dalva M. Silva Matos; Wayne Dawson; Rafael O. Xavier (Plant Ecology, 2021)

Bioactive and nutritional potential of Alaria esculenta and Saccharina latissima - C. Afonso; J. Matos; I. Guarda; A. Gomes-Bispo; R. Gomes; C. Cardoso; S. Gueifão; I. Delgado; I. Coelho; I. Castanheira; N. M. Bandarra (Journal of Applied Phycology, 2021)

Panicum maximum as a reservoir of a potential maize pathogen - N. C. Maia; M. P. Melo; S. S. C. Guimarães; K. S. Matos; S. I. Moreira; U. G. P. Lana; P. G. Cardoso (European Journal of Plant Pathology, 2021)

Δ9-Tetrahydrocannabinol (THC) Impairs CD8+ T Cell-Mediated Activation of Astrocytes - Joseph E. Henriquez; Anthony P. Bach; Karina M. Matos-Fernandez; Robert B. Crawford; Norbert E. Kaminski (Journal of Neuroimmune Pharmacology, 2020)

Treptacantha abies-marina (S.G. Gmelin) Kützing: Characterization and Application as a Whole Food Ingredient - C. Afonso; I. Guarda; M. Mourato; L.L. Martins; I. Fonseca; R. Gomes; J. Matos; A. Gomes; N.M. Bandarra; C. Cardoso (Journal of Aquatic Food Product Technology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Interaction of phytohormone-producing rhizobia with sugarcane mini-setts and their effect on plant development - Natália S. Ferreira; Gustavo F. Matos; Carlos H. S. G. Meneses; Veronica M. Reis; Janaina R. C. Rouws; Stefan Schwab; José I. Baldani; Luc F. M. Rouws (Plant and Soil, 2020)

Inorganic content of rock dust waste from northwest of Rio de Janeiro, Brazil: do environmental risks incur from its use as natural fertilizer? - Camila V. G. Vitó; Hellen G. Vieira; Adriano H. Ferrarez; Cibele M. S. de Almeida; Francisco L. F. da Silva; Wladiana O. Matos; Murilo de O. Souza (Environmental Monitoring and Assessment, 2020)

Seasonal variations in the diversity and structure of decapod communities in the changing hydrological scenario of the northwest African upwelling - Sidi M. Mohamed Moctar; Ana Ramos; Susana S. de Matos-Pita; Fran Ramil; Jens-Otto Krakstad (Marine Biodiversity, 2020)

Commercial Red Seaweed in Portugal (Gelidium sesquipedale and Pterocladiella capillacea, Florideophyceae): Going beyond a Single-Purpose Product Approach by Valorizing Bioactivity - J. Matos; A. Gomes; C. Cardoso; C. Afonso; A. M. Campos; R. Gomes; P. Falé; Inês Delgado; Inês Coelho; Isabel Castanheira; N. M. Bandarra (Thalassas: An International Journal of Marine Sciences, 2020)

Adenosine and NMDA Receptors Modulate Neuroprotection-Induced NMDA Preconditioning in Mice - Adriana B. Ghislandi; Michelle L. Garcez; Gabriela M. Zambon; Leandra C. Constantino; Douglas N. Matos; Bruna B. Pescador; Carla I. Tasca; Carina R. Boeck (Journal of Molecular Neuroscience, 2020)

Numerical modeling of free and submerged labyrinth weir flow for a large sidewall angle - José M. Carrillo; Jorge Matos; Ruth Lopes (Environmental Fluid Mechanics, 2020)

Lipid composition and some bioactivities of 3 newly isolated microalgae (Tetraselmis sp. IMP3, Tetraselmis sp. CTP4, and Skeletonema sp.) - C. Cardoso; H. Pereira; J. Franca; J. Matos; I. Monteiro; P. Pousão-Ferreira; A. Gomes; L. Barreira; J. Varela; N. Neng; J. M. Nogueira; C. Afonso; et al. (Aquaculture International, 2020)

Modulation of P2Y2 receptors in bovine cumulus oocyte complexes: effects on intracellular calcium, zona hardening and developmental competence - E. Fonseca; P. Mesquita; C. C. Marques; M. C. Baptista; J. Pimenta; J. E. Matos; G. Soveral; R. M. L. N. Pereira (Purinergic Signalling, 2020)

Do Workers from Subspecies Acromyrmex subterraneus Prepare Leaves and Toxic Baits in Similar Ways for Their Fungus Garden? - L. C. Forti; A. P. P. Andrade; K. K. A. Sousa; R. S. Camargo; C. A. O. Matos; N. Caldato; G. C. Catalani; V. M. Ramos (Neotropical Entomology, 2020)

Isotopes and geochemistry to assess shallow/thermal groundwater interaction in a karst/fissured-porous environment (Portugal): a review and reinterpretation - J. M. Marques; C. Matos; P. M. Carreira; M. O. Neves (Sustainable Water Resources Management, 2019)

Synthesis and in silico and in vitro evaluation of trimethoxy-benzamides designed as anti-prion derivatives - Raissa A. Conceição; Lucas M. Ascari; Natália C. Ferreira; Carolina F. Goes; Carolina O. Matos; Anderson S. Pinheiro; Marina A. Alves; Alessandra M. T. Souza; Rodolfo C. Maia; Byron Caughey; Yraima Cordeiro; Maria Letícia C. Barbosa (Medicinal Chemistry Research, 2019)

Spatial pattern of invasive and native graminoids in the Brazilian cerrado - Pavel Dodonov; Karen A. Harper; Rafael de Oliveira Xavier; Dalva M. Silva Matos (Plant Ecology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Effect of temperature on the thermal conductivity of a granite with high heat production from Central Portugal - M. M. Miranda; C. R. Matos; N. V. Rodrigues; A. J. S. C. Pereira; J. J. Costa (Journal of Iberian Geology, 2019)

Efficient biotechnological synthesis of flavor esters using a low-cost biocatalyst with immobilized Rhizomucor miehei lipase - Ulisses M. F. de Oliveira; Leonardo J. B. Lima de Matos; Maria Cristiane M. de Souza; Bruna B. Pinheiro; José C. S. dos Santos; Luciana R. B. Gonçalves (Molecular Biology Reports, 2019)

Purinergic system as a potential target for inflammation and toxicity induced by thymol in immune cells and tissues - Matheus D. Baldissera; Carine F. Souza; Antônio Francisco Igor M. De Matos; Bernardo Baldisserotto; Lenita M. Stefani; Aleksandro S. da Silva (Molecular and Cellular Biochemistry, 2019)

Electron paramagnetic resonance (EPR) spectroscopy as a tool for the characterization of biochar from guava waste - Tassya T. S. Matos; Antônio S. Mangrich; Estela M. C. Cardoso; Juliana Schultz; Mayara R. Fornari; Alberto Wisniewski; Ingrid S. C. Carregosa (Journal of Soils and Sediments, 2019)

Foraging strategies of a generalist seabird species, the yellow-legged gull, from GPS tracking and stable isotope analyses - Roberto F. Mendes; Jaime A. Ramos; Vitor H. Paiva; Joana G. Calado; Diana M. Matos; Filipe R. Ceia (Marine Biology, 2018)

Pre-hatching development in the intertidal zone negatively affects juvenile survival and physiology in the muricid gastropod Acanthina monodon - O. R. Chaparro; L. P. Salas-Yanquin; A. S. Matos; J. A. Bűchner-Miranda; M. W. Gray; V. M. Cubillos; J. A. Pechenik (Marine Biology, 2018)

Taxon cycle predictions supported by model‐based inference in Indo‐Pacific trap‐jaw ants (Hymenoptera: Formicidae: Odontomachus ) - Pável Matos‐Maraví; Nicholas J. Matzke; Fredrick J. Larabee; Ronald M. Clouse; Ward C. Wheeler; Daniela Magdalena Sorger; Andrew V. Suarez; Milan Janda (Molecular Ecology, 2018)
Nonequilibrium dynamics and non‐neutral processes, such as trait‐dependent dispersal, are often missing from quantitative island biogeography models despite their potential explanatory value. One of the most influential nonequilibrium models is the taxon cycle, but it has been difficult to test its validity as a general biogeographical framework. Here, we test predictions of the taxon cycle model using six expected phylogenetic patterns and a time‐calibrated phylogeny of Indo‐Pacific Odontomachus (Hymenoptera: Formicidae: Ponerinae), one of the ant genera that E.O. Wilson used when first proposing the hypothesis. We used model‐based inference and a newly developed trait‐dependent dispersal model to jointly estimate ancestral biogeography, ecology (habitat preferences for forest interiors, vs. “marginal” habitats, such as savannahs, shorelines, disturbed areas) and the linkage between ecology and dispersal rates. We found strong evidence that habitat shifts from forest interior to open and disturbed habitats increased macroevolutionary dispersal rate. In addition, lineages occupying open and disturbed habitats can give rise to both island endemics re‐occupying only forest interiors and taxa that re‐expand geographical ranges. The phylogenetic predictions outlined in this study can be used in future work to evaluate the relative weights of neutral (e.g., geographical distance and area) and non‐neutral (e.g., trait‐dependent dispersal) processes in historical biogeography and community ecology.

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

Life cycle assessment of aquafeed ingredients - Catarina Basto Silva; Luísa M. P. Valente; Elisabete Matos; Miguel Brandão; Belmira Neto (The International Journal of Life Cycle Assessment, 2018)

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

Towards Safer Data-Driven Forecasting of Extreme Streamflows - José P. Matos; Maria M. Portela; Anton J. Schleiss (Water Resources Management, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Importance of tissue sampling, laboratory methods, and patient characteristics for detection of Pneumocystis in autopsied lungs of non-immunosuppressed individuals - S. L. Vargas; C. Ponce; R. Bustamante; E. Calderón; G. Nevez; Y. De Armas; O. Matos; R. F. Miller; M. J. Gallo (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Ketamine Exhibits Different Neuroanatomical Profile After Mammalian Target of Rapamycin Inhibition in the Prefrontal Cortex: the Role of Inflammation and Oxidative Stress - Helena M. Abelaira; Gislaine Z. Réus; Zuleide M. Ignácio; Maria Augusta B. dos Santos; Airam B. de Moura; Danyela Matos; Júlia P. Demo; Júlia B. I. da Silva; Lucineia G. Danielski; Fabricia Petronilho; André F. Carvalho; João Quevedo (Molecular Neurobiology, 2017)

In Silico, In Vitro and In Vivo Toxicological Assessment of BPP-BrachyNH2, A Vasoactive Proline-Rich Oligopeptide from Brachycephalus ephippium - Daniel D. R. Arcanjo; Ana Carolina Mafud; Andreanne G. Vasconcelos; José Couras da Silva-Filho; Maurício P. M. Amaral; Lucas M. Brito; Marcelo P. Bemquerer; Selma A. S. Kückelhaus; Alexandra Plácido; Cristina Delerue-Matos; Nuno Vale; Yvonne P. Mascarenhas; et al. (International Journal of Peptide Research and Therapeutics, 2017)

Acute and chronic treatment with quetiapine induces antidepressant-like behavior and exerts antioxidant effects in the rat brain - Zuleide M. Ignácio; Gislaine Z. Réus; Helena M. Abelaira; Airam B. de Moura; Thays G. de Souza; Danyela Matos; Mariana P. Goldim; Khiany Mathias; Leandro Garbossa; Fabricia Petronilho; João Quevedo (Metabolic Brain Disease, 2017)

Tracing of aerosol sources in an urban environment using chemical, Sr isotope, and mineralogical characterization - Regina M. B. O. Duarte; João T. V. Matos; Andreia S. Paula; Sónia P. Lopes; Sara Ribeiro; José Francisco Santos; Carla Patinha; Eduardo Ferreira da Silva; Rosário Soares; Armando C. Duarte (Environmental Science and Pollution Research, 2017)

Severe Lead Toxicosis in a Lionhead Rabbit - Kristen M. Walter; Karyn Bischoff; Ricardo de Matos (Journal of Medical Toxicology, 2017)

Evaluation of Primary Production in the Lower Amazon River Based on a Dissolved Oxygen Stable Isotopic Mass Balance - William C. Gagne-Maynard; Nicholas D. Ward; Richard G. Keil; Henrique O. Sawakuchi; Alan C. Da Cunha; Vania Neu; Daimio C. Brito; Diani F. Da Silva Less; Joel E. M. Diniz; Aline De Matos Valerio; Milton Kampel; Alex V. Krusche; et al. (Frontiers in Marine Science, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Metagenomics unveils the attributes of the alginolytic guilds of sediments from four distant cold coastal environments - Marina N. Matos; Mariana Lozada; Luciano E. Anselmino; Matías A. Musumeci; Bernard Henrissat; Janet K. Jansson; Walter P. Mac Cormack; JoLynn Carroll; Sara Sjöling; Leif Lundgren; Hebe M. Dionisi (Environmental Microbiology, 2016)
Summary Alginates are abundant polysaccharides in brown algae that constitute an important energy source for marine heterotrophic bacteria. Despite the key role of alginate degradation processes in the marine carbon cycle, little information is available on the bacterial populations involved in these processes. The aim of this work was to gain a better understanding of alginate utilization capabilities in cold coastal environments. Sediment metagenomes from four high‐latitude regions of both Hemispheres were interrogated for alginate lyase gene homologue sequences and their genomic context. Sediments contained highly abundant and diverse bacterial assemblages with alginolytic potential, including members of Bacteroidetes and Proteobacteria , as well as several poorly characterized taxa. The microbial communities in Arctic and Antarctic sediments exhibited the most similar alginolytic profiles, whereas brackish sediments showed distinct structures with a higher proportion of novel genes. Examination of the gene neighbourhood of the alginate lyase homologues revealed distinct patterns depending on the potential lineage of the scaffolds, with evidence of evolutionary relationships among alginolytic gene clusters from Bacteroidetes and Proteobacteria . This information is relevant for understanding carbon fluxes in cold coastal environments and provides valuable information for the development of biotechnological applications from brown algae biomass.

New Trends in Food Allergens Detection: Toward Biosensing Strategies - Rita C. Alves; M. Fátima Barroso; María Begoña González-García; M. Beatriz P.P. Oliveira; Cristina Delerue-Matos (Critical Reviews in Food Science and Nutrition, 2016)

The application of lichens as ecological surrogates of air pollution in the subtropics: a case study in South Brazil - Natália M. Koch; Cristina Branquinho; Paula Matos; Pedro Pinho; Fabiane Lucheta; Suzana M. A. Martins; Vera M. F. Vargas (Environmental Science and Pollution Research, 2016)

A phylogeny of Lophocoleaceae-Plagiochilaceae-Brevianthaceae and a revised classification of Plagiochilaceae - Simon D. F. Patzak; Matt A. M. Renner; Alfons Schäfer-Verwimp; Kathrin Feldberg; Margaret M. Heslewood; Denilson F. Peralta; Aline Matos de Souza; Harald Schneider; Jochen Heinrichs (Organisms Diversity & Evolution, 2016)

High efficacy on diclofenac removal by activated carbon produced from potato peel waste - M. Bernardo; S. Rodrigues; N. Lapa; I. Matos; F. Lemos; M. K. S. Batista; A. P. Carvalho; I. Fonseca (International Journal of Environmental Science and Technology, 2016)

Riparian ecosystem configuration influences mesocarnivores presence in Mediterranean landscapes - Maria J. Santos; Luís M. Rosalino; Hugo M. Matos; Margarida Santos-Reis (European Journal of Wildlife Research, 2016)

Enhancing the biodiesel manufacturing process by use of glycerin to produce hyacinth fragrance - Cauê A. C. Silva; Flávia C. A. Figueiredo; Raphael Rodrigues; Mirela I. Sairre; Maraisa Gonçalves; Ines Matos; Isabel M. Fonseca; Dalmo Mandelli; Wagner A. Carvalho (Clean Technologies and Environmental Policy, 2016)

Molecular diversity and genetic relationships in Secale - E. SANTOS; M. MATOS; P. SILVA; A. M. FIGUEIRAS; C. BENITO; O. PINTO-CARNIDE (Journal of Genetics, 2016)

Mucoadhesive nanoparticles: a new perspective for fish drug application - A C da S Costa; H M Brandão; S R da Silva; A R Bentes‐Sousa; J A P Diniz; J de J Viana Pinheiro; M de F C de Melo; J O C Silva; E R Matos; R M Ribeiro‐Costa (Journal of Fish Diseases, 2016)

Structural and Functional Responses of Macrobenthic Communities to Mercury Contamination - P. Matos; E. Sousa; M. A. Pardal; E. Pereira; P. G. Cardoso (Water, Air, & Soil Pollution, 2016)

Behaviour and fate of metals in urban wastewater treatment plants: a review - P. Cantinho; M. Matos; M. A. Trancoso; M. M. Correia dos Santos (International Journal of Environmental Science and Technology, 2016)

Economic Analysis of a Rainwater Harvesting System in a Commercial Building - C. Matos; I. Bentes; C. Santos; M. Imteaz; S. Pereira (Water Resources Management, 2015)

Blocking ELISA Using Recombinant NcSRS2 Protein for Diagnosing Bovine Neosporosis - Francine A. Sinnott; Leonardo G. Monte; Thais F. Collares; Bruno M. De Matos; Diene B. Pacheco; Sibele Borsuk; Renato Andreotti; Cláudia P. Hartleben (Current Microbiology, 2015)

New Thermoresistant Polymorph from CO2 Recrystallization of Minocycline Hydrochloride - Miguel A. Rodrigues; João M. Tiago; Luis Padrela; Henrique A. Matos; Teresa G. Nunes; Lídia Pinheiro; António J. Almeida; Edmundo Gomes de Azevedo (Pharmaceutical Research, 2014)

Blockade of proteinase-activated receptor 4 inhibits neutrophil recruitment in experimental inflammation in mice - Lindisley F. Gomides; Onésia C. O. Lima; Natália A. Matos; Kátia M. Freitas; Janetti Nogueira Francischi; Juliana Carvalho Tavares; André Klein (Inflammation Research, 2014)

Multiple Linear Regression and Artificial Neural Networks to Predict Time and Efficiency of Soil Vapor Extraction - José Tomás Albergaria; F. G. Martins; M. C. M. Alvim-Ferraz; C. Delerue-Matos (Water, Air, & Soil Pollution, 2014)

(1–3)-Beta-D-glucan in association with lactate dehydrogenase as biomarkers of Pneumocystis pneumonia (PcP) in HIV-infected patients - F. Esteves; C.-H. Lee; B. de Sousa; R. Badura; M. Seringa; C. Fernandes; J. F. Gaspar; F. Antunes; O. Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Cu- and Zn-Soil Anomalies in the NE Border of the South Portuguese Zone (Iberian Variscides, Portugal) Identified by Multifractal and Geostatistical Analyses - F. Luz; A. Mateus; J. X. Matos; M. A. Gonçalves (Natural Resources Research, 2014)

Structural requirements of glycosaminoglycans for their interaction with HIV-1 envelope glycoprotein gp120 - Pedro M. Matos; David Andreu; Nuno C. Santos; Ricardo Gutiérrez-Gallego (Archives of Virology, 2014)

The role of edge contrast and forest structure in edge influence: vegetation and microclimate at edges in the Brazilian cerrado - Pavel Dodonov; Karen A. Harper; Dalva M. Silva-Matos (Plant Ecology, 2013)

Reproducibility of Positive Results for the Detection of Serum Galactomannan by Platelia™ Aspergillus EIA - Kelly C. M. C. Pedroza; Sócrates B. de Matos; Daniel L. de Moura; Mônica B. B. Oliveira; Marco A. S. Araújo; Roberto J. M. Nascimento; Fernanda W. M. Lima (Mycopathologia, 2013)

Geology of the Rosário–Neves Corvo antiform, Iberian Pyrite Belt, Portugal: new insights from physical volcanology, palynostratigraphy and isotope geochronology studies - J. T. Oliveira; C. J. P. Rosa; Z. Pereira; D. R. N. Rosa; J. X. Matos; C. M. C. Inverno; T. Andersen (Mineralium Deposita, 2013)

A DNA methylation signature associated with the epigenetic repression of glycine N-methyltransferase in human hepatocellular carcinoma - Covadonga Huidobro; Estela G. Toraño; Agustín F. Fernández; Rocío G. Urdinguio; Ramón M. Rodríguez; Cecilia Ferrero; Pablo Martínez-Camblor; Loreto Boix; Jordi Bruix; Juan Luís García-Rodríguez; Marta Varela-Rey; José María Mato; et al. (Journal of Molecular Medicine, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Pilot monitoring study of ibuprofen in surface waters of north of Portugal - Paula Paíga; Lúcia H. M. L. M. Santos; Célia G. Amorim; Alberto N. Araújo; M. Conceição B. S. M. Montenegro; Angelina Pena; Cristina Delerue-Matos (Environmental Science and Pollution Research, 2013)

Interleukin-6 gene −174G>C and −636G>C promoter polymorphisms and prostate cancer risk - J. F. Magalhães; A. J. Cortinhas; C. M. Albuquerque; C. S. Baptista; R. Ribeiro; Carlos Viegas; Augusto Matos; João Machado; Maria A. Pires; Henrique Guedes-Pinto; A. Martins-Bessa; J. C. Leitão; et al. (Molecular Biology Reports, 2013)

Euptychia boulleti (Le Cerf) n. comb. (Lepidoptera: Nymphalidae: Satyrinae), a Rare and Endangered Butterfly from Southeastern Brazil - A V L Freitas; N Wahlberg; P F Matos-Maravi; M A Marin; O H H Mielke (Neotropical Entomology, 2012)

Sequential Application of Soil Vapor Extraction and Bioremediation Processes for the Remediation of Ethylbenzene-Contaminated Soils - António Alves Soares; Maria Teresa Pinho; José Tomás Albergaria; Valentina Domingues; Maria da Conceição M. Alvim-Ferraz; Paolo De Marco; Cristina Delerue-Matos (Water, Air, & Soil Pollution, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

A signature of six genes highlights defects on cell growth and specific metabolic pathways in murine and human hepatocellular carcinoma - Paul C. Schröder; Víctor Segura; José Ignacio Riezu; Bruno Sangro; José M. Mato; Jesús Prieto; Enrique Santamaría; Fernando J. Corrales (Functional & Integrative Genomics, 2011)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

Alcohol and tobacco, and the risk of cancers of the upper aerodigestive tract in Latin America: a case–control study - K. Szymańska; R. J. Hung; V. Wünsch-Filho; J. Eluf-Neto; M. P. Curado; S. Koifman; E. Matos; A. Menezes; L. Fernandez; A. W. Daudt; P. Boffetta; P. Brennan (Cancer Causes & Control, 2011)

Steady-state level of epidermal growth factor (EGF) mRNA and effect of EGF on in vitro culture of caprine preantral follicles - Juliana Jales H. Celestino; Jamily B. Bruno; Márcia Viviane A. Saraiva; Rebeca M. P. Rocha; Ivina R. Brito; Ana Beatriz G. Duarte; Valdevane R. Araújo; Cleidson M. G. Silva; Maria Helena T. Matos; Claudio C. Campello; José Roberto V. Silva; José Ricardo Figueiredo (Cell and Tissue Research, 2011)

Using zeta-potential measurements to quantify peptide partition to lipid membranes - João M. Freire; Marco M. Domingues; Joana Matos; Manuel N. Melo; Ana Salomé Veiga; Nuno C. Santos; Miguel A. R. B. Castanho (European Biophysics Journal, 2011)

Estimation of pollutant partition in sandy soils with different water contents - José Tomás Albergaria; Maria da Conceição M. Alvim-Ferraz; Maria Cristina F. Delerue-Matos (Environmental Monitoring and Assessment, 2010)

Comparative anticonvulsant activities of the essential oils (EOs) from Cymbopogon winterianus Jowitt and Cymbopogon citratus (DC) Stapf. in mice - Monalisa Ribeiro Silva; Rafael Matos Ximenes; José Galberto Martins da Costa; L. Kalyne A. M. Leal; Amanda A. de Lopes; Glauce Socorro de Barros Viana (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Kalirin: a novel genetic risk factor for ischemic stroke - Tiago Krug; Helena Manso; Liliana Gouveia; João Sobral; Joana M. Xavier; Isabel Albergaria; Gisela Gaspar; Manuel Correia; Miguel Viana-Baptista; Rita Moiron Simões; Amélia Nogueira Pinto; Ricardo Taipa; et al. (Human Genetics, 2010)

An easier method to identify the individual genomic composition of allopolyploid complexes - A. Inácio; I. Matos; M. P. Machado; M. M. Coelho (Journal of Fish Biology, 2010)
A new method for the fast identification of the genomic composition of the cyprinid Squalius alburnoides is presented. The method is based on a length polymorphism detected in the β‐actin gene, which serves as the basis for the development of a semi‐quantitative PCR.

An anti-inflammatory lectin from Luetzelburgia auriculata seeds inhibits adhesion and rolling of leukocytes and modulates histamine and PGE2 action in acute inflammation models - N. M. N. Alencar; R. S. B. Oliveira; J. G. Figueiredo; I. J. M. Cavalcante; M. P. V. Matos; F. Q. Cunha; J. V. S. Nunes; L. R. Bomfim; M. V. Ramos (Inflammation Research, 2010)

Scaleprinting: individual identification based on scale patterns - M. Morgado‐Santos; I. Matos; L. Vicente; M. J. Collares‐Pereira (Journal of Fish Biology, 2010)
A non‐intrusive method for individual identification of Iberian cyprinid complex Squalius alburnoides is presented, with possible application to other fish complexes and species. The proposed methodology is based on scale patterns that vary greatly between individuals.

sTNFR-1 is an early inflammatory marker in community versus institutionalized elderly women - Fernanda Matos Coelho; F. M. S. Narciso; D. M. G. Oliveira; D. S. Pereira; A. L. Teixeira; M. M. Teixeira; D. G. Souza; L. S. M. Pereira (Inflammation Research, 2010)

Variable number tandem repeat loci providing discrimination within widespread genotypes of Acinetobacter baumannii - J. F. Turton; J. Matos; M. E. Kaufmann; T. L. Pitt (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Genetic characterization of the UCS and Kex1 loci of Pneumocystis jirovecii - F. Esteves; A. Tavares; M. C. Costa; J. Gaspar; F. Antunes; O. Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Does riparian habitat condition influence mammalian carnivore abundance in Mediterranean ecosystems? - Hugo M. Matos; Maria J. Santos; Francisco Palomares; Margarida Santos-Reis (Biodiversity and Conservation, 2009)

Assessing dam implementation impact on threatened carnivores: the case of Alqueva in SE Portugal - Maria J. Santos; Nuno M. Pedroso; Joaquim P. Ferreira; Hugo M. Matos; Teresa Sales-Luís; Íris Pereira; Carla Baltazar; Clara Grilo; Ana T. Cândido; Inês Sousa; Margarida Santos-Reis (Environmental Monitoring and Assessment, 2008)

Distal colonic Na+ absorption inhibited by luminal P2Y2 receptors - J. E. Matos; M. V. Sorensen; C. S. Geyti; B. Robaye; J. M. Boeynaems; J. Leipziger (Pflügers Archiv - European Journal of Physiology, 2007)

The invasion of Pteridium aquilinum and the impoverishment of the seed bank in fire prone areas of Brazilian Atlantic Forest - Úrsula Souza Rodrigues da de Silva; Dalva M. da Silva Matos (Biodiversity and Conservation, 2006)

A Glycine N-methyltransferase Knockout Mouse Model for Humans with Deficiency of this Enzyme - Zigmund Luka; Antonieta Capdevila; José M. Mato; C. Wagner (Transgenic Research, 2006)

Cervical cancer and CYP2E1 polymorphisms: implications for molecular epidemiology - Paula M. Ferreira; Raquel Catarino; Deolinda Pereira; Ana Matos; Daniela Pinto; Ana Coelho; Carlos Lopes; Rui Medeiros (European Journal of Clinical Pharmacology, 2006)

A new aluminum tolerance gene located on rye chromosome arm 7RS - M. Matos; M. V. Camacho; V. Pérez-Flores; B. Pernaute; O. Pinto-Carnide; C. Benito (Theoretical and Applied Genetics, 2005)

Secale cereale inter-microsatellites (SCIMs): chromosomal location and genetic inheritance - M. V. Camacho; M. Matos; C. Gonzlez; V. Prez-Flores; B. Pernaute; O. Pinto-Carnide; C. Benito (Genetica, 2005)

Cholesterol depletion by methyl-?-cyclodextrin enhances myoblast fusion and induces the formation of myotubes with disorganized nuclei - Cludia S. Mermelstein; Dbora M. Portilho; Rommel B. Medeiros; Aline R. Matos; Marcelo Einicker-Lamas; Giovane G. Tortelote; Adalberto Vieyra; Manoel L. Costa (Cell and Tissue Research, 2005)

Assessment of Water Systems for Contaminants from Domestic and Industrial Sewages - C. P. Jordão; M. G. Pereira; C. R. Bellato; J. L. Pereira; A. T. Matos (Environmental Monitoring and Assessment, 2002)

Understanding the threats to biological diversity in southeastern Brazil - Dalva M. Silva Matos; Marilene L.A. Bovi (Biodiversity and Conservation, 2002)

Effect of Oral Washes on the Diagnosis of Pneumocystis carinii Pneumonia with a Low Parasite Burden and on Detection of Organisms in Subclinical Infections - O. Matos; M. Costa; B. Lundgren; L. Caldeira; P. Aguiar; F. Antunes (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

A novel germline mutation in exon 5 of the multiple endocrine neoplasia type 1 gene - A. Chico; Luis Gallart; Eugenia Mato; Carmen Mayoral; Jesus M. Martin-Campos; Lluís Catasús; Jose Rodriguez-Espinosa; Xavier Matías-Guiu; Francisco Blanco-Vaca; Alberto de Leiva (Journal of Molecular Medicine, 1998)

Geology and geophysics as successful tools in the discovery of the Lagoa Salgada Orebody (Sado Tertiary Basin - Iberian Pyrite Belt), Grndola, Portugal - V. Oliveira; J. Matos; M. Bengala; N. Silva; P. Sousa; L. Torres (Mineralium Deposita, 1997)